Internal control of fixed assets : a controller and auditor's guide - King, Alfred M. (Hoboken, N.J. : Wiley, 2011)
"For many companies, fixed assets represent the largest single aspect of their financial statement, yet rarely do they command time proportionate to the magnitude of the investment. This is the first book to show how to implement internal controls for fixed assets. It is a step-by-step guide for developing and maintaining a functioning internal control system that will withstand the closest scrutiny from independent public accountants and the PCAOB. With up-to-the-minute discussion of IFRS and GAAP, this is a must-have guide for controllers, auditors, and CFOs"--
Front Matter -- Internal Control, Sarbanes-Oxley, and the Public Company Accounting Oversight Board -- Capitalization versus Expense -- Asset Life Cycle--Controls and Software -- Depreciation and Amortization for Books and Taxes -- Impairment Testing -- Physical Control of Property, Plant, and Equipment -- Taking a Physical Inventory -- Reconciliation of Physical Inventory to Accounting Records -- Fixed Assets in a Business Combination -- Insurance for Fixed Assets -- Property Taxes--Personal Property and Real Estate -- Developing the Fair Value of Fixed Assets -- Control of Fixed Assets under International Financial Reporting Standards -- Component Depreciation for Buildings -- Appendix: Excerpt of Internal Revenue Service Cost Segregation Audit Guide -- About the Author -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Capital; Accounting; Accounting; Capital; BUSINESS & ECONOMICS -- Investments & Securities -- General; Accounting; Capital; Electronic books